Pengaruh Strategi Kebijakan Dan Pemberlakuan Insentif Pajak Terhadap Optimalisasi Penerimaan Pajak Di Masa Pandemi Covid-19 Pada Kantor Pelayanan Pajak (KPP) Pratama Tigaraksa Tahun 2020 - Dimas Cikal Bagyawan; Erni Prasetiyani (Jurnal Ilmu Administrasi Publik, 2022)
Policy strategies through tax incentives hope to stabilize the economic sector. In the report on the realization of the Small Taxpayers Office of Tigaraksa in 2020 with a growth rate of -57.42 percent or 3.36 trillion, this is far from the growth in 2019, which was 4.48 trillion. This research is quantitative research with descriptive analysis carried out at Small Taxpayers Office of Tigaraksa. This study aims to find out how much influence policy strategies and the application of tax incentives have on tax revenues at Small Taxpayers Office of Tigaraksa. This research uses primary data, by distributing questionnaires as research material, the results of the research proved that the hypothesis test on the Strategy Variable has a negative effect, the tax incentive Variable has a partial positive effect, the Strategy and Tax Incentive has a simultaneous positive effect on Tax Revenue at Small Taxpayers Office of Tigaraksa for 2020.